2008
DOI: 10.1002/dev.20252
|View full text |Cite
|
Sign up to set email alerts
|

Early adolescents show enhanced acute cocaine‐induced locomotor activity in comparison to late adolescent and adult rats

Abstract: Initiation of drug use during adolescence is associated with an increased probability to develop a drug addiction. The present study examined dose-response effects of cocaine (0, 5, 10, or 20 mg/kg, i.p.) on locomotor activity in early adolescent (postnatal day (PND) 35), late adolescent (PND 45), and young adults (PND 60) by measuring total distance moved (TDM) and frequency of start-stops. In response to 20 mg/kg cocaine, early adolescents showed the greatest cocaineinduced increase in TDM in comparison to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
3
27
0
2
Order By: Relevance
“…In this group, cocaine increased locomotor activity on the first day of treatment, and this effect progressively increased over subsequent days of testing. These findings are consistent with a large number of studies examining the locomotor effects of cocaine after acute (Waddell and Holtzman, 1998;Badanich et al, 2008) and repeated (Laviola et al, 1995;Sabeti et al, 2003) administration. Effects of Opioids.…”
Section: Discussionsupporting
confidence: 90%
“…In this group, cocaine increased locomotor activity on the first day of treatment, and this effect progressively increased over subsequent days of testing. These findings are consistent with a large number of studies examining the locomotor effects of cocaine after acute (Waddell and Holtzman, 1998;Badanich et al, 2008) and repeated (Laviola et al, 1995;Sabeti et al, 2003) administration. Effects of Opioids.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to what is seen with the D2 agonists, there is an increase as the animals approach 20-35 days of age and then a decrease to the adult values ( fig. 6 d) [Spear and Brake, 1983;Collins and Izenwasser, 2004;Caster et al, 2005Caster et al, , 2007Kirstein, 2005, 2007;Frantz et al, 2007;Badanich et al, 2008;Parylak et al, 2008;Smith and Morrell, 2008]. These data support a D2 over D1 predominance in locomotion and possibly mRNA at the time periods where we see negative rCBV responses to cocaine or MPH, indicating the functional predominance of the D2 effects.…”
Section: Meta-analysis Of Literature Datasupporting
confidence: 72%
“…Adolescents have also been reported to show enhanced cocaineinduced locomotor activity relative to late adolescent and adult rats (Badanich and Kirstein, 2004;Badanich et al, 2008). In another study, no clear effect of nicotine on locomotion was, however, found in adolescent rats, while similar doses in late adolescence and adulthood suppressed locomotion (Belluzzi et al, 2004).…”
Section: Discussionmentioning
confidence: 94%